AN ANALYSIS OF STUDENTS’ LEARNING STRATEGIES IN OVERCOMING PASSIVE VOICE ERRORS - Fauzi Hamsul; Irfan Hamonangan Tarihoran (STKIP Paracendekia NW Sumbawa, 2024)
This article investigates the learning strategies employed by students at STKIP Paracendekia NW Sumbawa to overcome errors in constructing passive voice sentences. The study focuses on identifying the types of errors made by students and the strategies they utilize to correct these errors. Data was collected through interviews and the analysis of students' written exercises. The results reveal that students predominantly encounter misformation and omission errors when constructing passive voice sentences. These errors often stem from a lack of understanding of verb conjugations and the omission of auxiliary verbs. The study further explores the learning strategies used by students, categorized according to Oxford's (1990) classification, including cognitive, metacognitive, affective, and social strategies. It was found that students frequently employ cognitive strategies, such as seeking out resources and practicing sentence construction, as well as social strategies, including consulting peers and instructors. The findings suggest that while students are aware of the importance of using correct passive voice structures, they still struggle with certain aspects of its application. The study concludes by recommending targeted instructional strategies to improve students' understanding and use of passive voice, thereby enhancing their overall proficiency in English grammar